Pengaruh City Branding “Pasuruan The City of Madinah” Dan Viral Marketing Terhadap Keputusan Berkunjung Dan Dampaknya Pada Minat Berkunjung Kembali - Miftahul Huda; Khasanatul Abidah (Economic Reviews Journal, 2024)
The aim of this research is to determine and measure the influence of city branding "Pasuruan of Madinah" and viral marketing on the decision to visit and interest in returning to Pasuruan City Square. This research is a quantitative study with a sample size of 116 respondents using a purposive sampling technique with an analysis tool, namely SPSS version 25. The results of the research show that City Branding has a significant effect on the Decision to Visit, Viral Marketing has a significant effect on the Decision to Visit, City Branding has a significant effect on Interest in Visiting Again, Viral Marketing has a significant influence on Interest in Returning to Visit, City Branding through the Decision to Visit Again has a significant influence on Interest in Returning to Visit, and Viral Marketing through the Decision to Visit Again has a significant influence on Interest in Returning to Visit.